Promoting Decent Work and Equal Pay in the Informal Agricultural Sector: A Gender Perspective - Shrestha, Prabin; Bhandari, Gaurav; Rai, Melija; Khadka, Nirajan; Rai, Shanti; Tamrakar, Shristi; Khanal, Avishek; Giri, Suja (Journal of Sustainability and Environmental Management, 2024)
Agriculture, the oldest human activity, is the livelihood for millions, especially in developing countries where it drives economic growth and poverty reduction. However, the informal agricultural sector lacks poor working conditions, low wages, lack of legal protection, and significant gender-based discrimination. Women often face unequal access to resources, training, and fair wages, perpetuating a cycle of poverty. This review paper examines decent work and equal pay in the informal agricultural sector, focusing on gender disparities, and offers recommendations to promote gender equality, empowerment, and sustainable development through targeted interventions and policy improvements. The study used the PRISMA model for a systematic literature review. The study highlighted the five dimensions of decent work identified by the ILO, providing a comprehensive framework for understanding and addressing challenges in achieving decent work. The review also identified several factors influencing decent work and equal pay, including government policies, market dynamics, social norms, power dynamics, and social security programs. The review further discussed the gender dimension of decent work and equal pay, highlighting the gender wage gap and the challenges faced by women in accessing decent work and fair compensation in the sector. Innovative approaches to promoting decent work and equal pay were also discussed, including social protection programs, collective bargaining, microfinance initiatives, vocational training, and digital tools.